Expression of cellobiose dehydrogenase gene in Aspergillus niger C112 and its effect on lignocellulose degrading enzymes - Zhong, Yanan; Guo, Zepan; Li, Meiqun; Jia, Xiaojiang; Zeng, Baiquan (Frontiers in Microbiology, 2024)
Cellobiose dehydrogenase (CDH) is one of the cellulase auxiliary proteins, which is widely used in the field of biomass degradation. However, how to efficiently and cheaply apply it in industrial production still needs further research. Aspergillus niger C112 (A. niger C112) is a significant producer of cellulase and has a relatively complete lignocellulose degradation system, but its CDH activity was only 3.92 U. To obtain a recombinant strain of A. niger C112 with high cellulases activity, the CDH from the readily available white-rot fungus Grifola frondose had been heterologously expressed in A. niger C112, under the control of the gpdA promoter. After cultivation in the medium with alkali-pretreated poplar fiber as substrate, the enzyme activity of recombinant CDH reached 36.63 U/L. Compared with the original A. niger C112, the recombinant A. niger transformed with Grifola frondosa CDH showed stronger lignocellulase activity, the activities of cellulases, β-1, 4-glucosidase and manganese peroxidase increased by 28.57%, 35.07% and 121.69%, respectively. The result showed that the expression of the gcdh gene in A. niger C112 could improve the activity of some lignocellulose degrading enzymes. This work provides a theoretical basis for the further application of gcdh gene in improving biomass conversion efficiency. pUCm-T, and sequenced by Beijing Genomics institution. Compare and analyze the gene sequencing results of gcdh with the published gcdh sequences of Grifola frondosa on the online website NCBI BLAST.